The Role and Mechanism of Protein Post‑Translational Modification in Rheumatoid Arthritis - Wen J; Liu J; Wan L; Wang F (Journal of Inflammation Research, 2025)
Jianting Wen,1– 3 Jian Liu,1– 3 Lei Wan,1– 3 Fanfan Wang2,3 1Department of Rheumatology and Immunology, First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, 230031, People’s Republic of China; 2Institute of Rheumatology, Anhui Academy of Chinese Medicine, Hefei, Anhui Province, 230012, People’s Republic of China; 3Anhui Province Key Laboratory of Modern Chinese Medicine Department of Internal Medicine Application Foundation Research and Development, Hefei, Anhui, 230031, People’s Republic of ChinaCorrespondence: Jian Liu, Department of Rheumatology and Immunology, First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, 230031, People’s Republic of China, Tel +86 0551 62838582, Fax +86 0551 62821605, Email liujianahzy@126.comAbstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that significantly compromises patient quality of life due to its high prevalence and risk of disability. While its etiology remains incompletely understood, increasing evidence highlights the critical involvement of epigenetic mechanisms, particularly post-translational modifications (PTMs), in RA pathogenesis. Advances in proteomics have identified various PTMs—including phosphorylation, methylation, acetylation, ubiquitination, glycosylation, lactylation, as well as citrullination and carbamylation—as key regulators of inflammation, immune response, and tissue remodeling in RA. Importantly, dysregulated PTMs may alter protein structure and function, thereby contributing to disease progression. This review systematically summarizes current knowledge on the roles and mechanisms of major PTMs in RA, with a special focus on the cross-talk between PTMs, their interaction with non-coding RNAs, and the emerging therapeutic potential of traditional Chinese medicine (TCM) targeting PTMs. These insights may provide novel perspectives for the diagnosis and treatment of RA.Keywords: protein post-translational modification, rheumatoid arthritis, methylation, acetylation, lactylation